FILSAFAT POLITIK NURCHOLISH MADJID - Tajuddin, Muhammad Saleh (JPP (Jurnal Politik Profetik), 2021)
The research emphasized the political philosophy of Nurcholish Madjid, a contemporary Islamic scholar, who had a strong influence among the young scholars in Indonesia. The study aims to describe the philosophy of Islamic politics by Nurcholish Madjid particularly the concept of secularization and civil society. By using qualitative data, particularly the library research method through books and academic journal, the study resulted the idea of civil society had a root from Islamic citizen which was built by Prophet Muhammad SAW in Madina, 570 C. The civil society was translated into the term “Masyarakat Madani” which including some aspects: egality, respect to others, actively participating in the society, rely on law and justice, tolerance and pluralism, and deliberation. In order to explain his secularization philosophy, Nurcholish gave a justification from Islamic teaching through confession of faith (syahada), which told that people were free from various beliefs, then strengthen their belief to the real God.